The Influence of Knowledge Management on the Attitudes and Perceptions of Graduate Students Toward Learning at a Public University According to the Knowledge Spiral - Surco Salinas, Daniel Victor (2024)
The objective of this research was to demonstrate the influence of knowledge management on the attitudes and perceptions toward learning among students enrolled in an Industrial Engineering doctoral program of a public university. The study follows the knowledge spiral model and adopts an applied and quantitative approach with a quasi-experimental, explanatory design. The sample consists of all the doctoral students enrolled in the program, and the study uses a census sample of 22 students. Although two specific hypotheses presented negative results, the study finds that the attitudes and perceptions of students toward the combination and internalization of knowledge have exceeded expectations, albeit with a lower baseline than initially proposed. However, the study suggests that there is still room for improvement in knowledge management practices.